2012
DOI: 10.1097/bcr.0b013e31823359ae
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Oscillatory Ventilators in Burn Patients

Abstract: The objective of the study is to review a single institution's experience with high-frequency oscillatory ventilation (HFOV) and compare patient characteristics, outcomes, and complications with other reported studies of HFOV use in burn patients with acute respiratory distress syndrome and respiratory failure. This study is a retrospective chart review of the burn patients treated with HFOV in Pediatric Burn Unit at Riley Hospital for Children from October 1996 to April 2007. Patient data were collected, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
1
5
0
2
Order By: Relevance
“…High-frequency oscillatory ventilation (HFOV) is a mode of MV which shares some features with HFPV [24]. Although HFOV is no longer recommended for the treatment of ARDS in adults [25,26] or children [27], it has been used for children with burns and/or inhalation injuries [28][29][30]. Most literature regarding the use of HFOV in this population has been limited to small, single-center, retrospective studies [28].…”
Section: High-frequency Percussive Ventilationmentioning
confidence: 99%
“…High-frequency oscillatory ventilation (HFOV) is a mode of MV which shares some features with HFPV [24]. Although HFOV is no longer recommended for the treatment of ARDS in adults [25,26] or children [27], it has been used for children with burns and/or inhalation injuries [28][29][30]. Most literature regarding the use of HFOV in this population has been limited to small, single-center, retrospective studies [28].…”
Section: High-frequency Percussive Ventilationmentioning
confidence: 99%
“…Существует много литературы с доводами против использования HFOV (высокочастотная осцилляторная вентиляция) [27,30]. К недостаткам HFOV относятся технические сложности аспирации секрета, наличие большого количества способов увеличения объема легких, скопление газов, бронхоспазм и стимуляция образования экссудата и агрегатов [30,31]. Другие отрицательные моменты использования HFOV у детей с ингаляционными травмами связаны с трудностями в проведении ингаляционной (аэрозольной) терапии и с высокой вероятностью возникновения баротравмы [31].…”
Section: стратегии ивлunclassified
“…80 Alveolar ventilation is enhanced by increasing the power and decreasing the frequency of oscillation. 80 Initial reports of the usefulness of HFOV appeared promising, 39,81 but with more clinical experience, it became apparent that HFOV had many limitations and few advantages when used as a rescue therapy in the setting of smoke inhalation injury. When used for SI-ALI, it has been reported that improvements in oxygenation are attenuated, 80,82 the risk of severe hypercapnia may be increased, 82 and adjunctive therapy including bronchodilators, inhaled heparin, and N-acetyl cysteine may not be instituted.…”
Section: Salvage Ventilation Strategies (Hfv)mentioning
confidence: 99%
“…The available lower quality evidence that was not included, however, does not support the efficacy of HFOV to treat patients with SI-ALI and suggests that it may be detrimental in this population. 39,80,82 It is unclear whether the failure of patients to improve in these studies is a direct consequence of the ventilation mode or because it precludes the aggressive pulmonary "toilette" and nebulization therapies that have been reported to improve outcomes in patients with SI-ALI. 16,18,50 High-frequency percussive ventilation.…”
Section: Salvage Ventilation Strategies (Hfv)mentioning
confidence: 99%
See 1 more Smart Citation